3D visualization of the joints using MR images. - Huang, Grace Manjun. (2009)
Most images are 2D in nature and thus surgeons have to use multiple images (aligning or comparing them) in order to construct a 3D model from their imagination for surgery. Traditionally, a radiologist supposed to diagnose such data sets would look at the scanned images slice by slice. By mentally reconstructing the sampled information into a three-dimensional representation, he would judge on the health of the patient. (König et al., 2001) However, we know that in science, and more specifically in the application of medicine, we need to quantify the methods and having a qualitative analysis is definitely insufficient.